Qualidade de Coffea canephora associada a análises agronômicas, físico-químicas, sensoriais e moleculares - Souza, Lucimara Cruz de (2021)
Coffee is one of the main commodities in Brazil, being the species Coffea canephora, a highlight of productivity in agribusiness in the state of Espírito Santo, where it is referred to as conilon coffee. Agronomic, physical-chemical, sensory and molecular analysis of coffee trees allow directing the choice of accessions that combine genetic diversity, good agronomic performance and superior cup quality. The objective of this study was to characterize genotypes (parents and hybrid progenies) of conilon coffee from the breeding program of the Instituto Capixaba de Pesquisa, Assistência Técnica e Extensão Rural (Incaper), from an experiment with six years of age, in 2017, conducted at the Experimental Farm in Marilândia, ES. The genotypes were evaluated by different attributes related to quality (agronomic, physical-chemical and sensory) and, molecular markers. Molecular analyzes were performed with 18 Simple Sequence Repeat - SSR markers and 11 parents with 101 hybrid progenies. A total of 32 alleles were obtained and the markers were classified as moderately informative (PIC = 0.37). High genetic variability was observed between parents and progenies. The dissimilarity values varied from 0.08 (P1 and P5) to 0.45 (P2 and P11) (mean = 0.29) for the parents and from 0.00 (8 and 9) to 0.65 (4 and 40) (mean = 0.34) for the progenies. Progenies 38 and 40 and father P11 were considered the most divergent in the study. Progenies 8 and 9 were considered duplicates. The quality analyzes were performed with 6 parents and 101 hybrid progenies and included 34 variables (agronomic, physicalchemical and sensory). Complementing the characterization and multivariate analyzes of these variables, an association study was made with 14 SSR markers, considered polymorphic in the molecular analyses, aiming to identify possible loci involved in quality control. On average, the genotypes were characterized as of medium and uniform maturation, medium sized fruits, good processing yield and with a high percentage of flat grains and mocha. It was observed that many genotypes presented small grains. In the physical-chemical analyses, sucrose showed average values (1.92%) below that expected for conilon coffee (3% to 7%), and chlorogenic acids (4.82%) and caffeine (2.58%) were the ones with the highest concentrations. In the sensory analyses, 34 genotypes were classified as special and/or fine coffees, with scores ≥ 80 points. The cup of parents and progenies was scored on average with 78.88 points. The treatments with higher sensory notes showed lower values of acidity, electrical conductivity, potassium leaching, chlorogenic acids, caffeine and higher sucrose values, indicating that these attributes are related to the sensory quality of the cup. In the associative analysis, 13 molecular markers were significantly associated with the variables studied in the scope of quality, which indicates a possible connection of these marks with QTLs involved in the control of characteristics. In the multivariate analyses, there was wide variability between the genotypes, with emphasis on the 34 with sensory scores ≥ 80 points, which were shown to be superior agronomically within the set of variables studied and, with genetic divergence. The joint results indicate the existence of genetic variability for the evaluated attributes, which can be explored in the genetic improvement of conilon coffee for the selection of plants that have superior characteristics related to quality and at the molecular level.